Working in partnership : best practice in customer-supplier relations - Burnes, Bernard. 1953-; Dale, B. G. (Gower, 1998)
Using the experience of practising managers, this book offers advice on developing working partnerships with customers and suppliers. Focusing on the public sector, the automotive and leisure industries, the book examines all issues including different types of partnership and their benefits.